An Interview with Dr. Sandip Shah; President of Independent Power Producers Association of Nepal (IPPAN) - Thanju, Jeevan P (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Not available. Interview with Dr. Sandip Shah; President of Independent Power Producers Association of Nepal (IPPAN) DOI: 10.3126/hn.v7i0.4243 Hydro Nepal Journal of Water, Energy and Environment Vol. 7, July, 2010 Page: 92-94 Uploaded date: 31 January, 2011